Le sceau d’Agamemnon - Nicolas Siron (Images Re-Vues)
Recent research in Ancient history focuses on the life of objects, as circulation and the reuse of artifacts, and the image of statues, whose biography can be traced. The seal of Agamemnon, mentioned in Aeschylus, Sophocles and Euripides, raises this question in a different way: as a fictional object, its progressive elaboration during the 5th century bc responds to an intertextual logic but also to strategies that entrust it with a function that is each time specific. The various tragic passages then provide an opportunity to reexamine the uses of seals in classical Athens, between closing, recognition, identification and accreditation of a message or the integrity of a container. Such a reconstruction balances the archaeological seals, whose images alone are known, and the attic vases, which very rarely represent seals and amulets and never the iconography they might display.